From Evidence to Policy Supporting Nepal’s Trade Integration Strategy : Trade Imbalances and Remittances - Portugal, Alberto; Zildzovic, Emir (World Bank, Washington, DC, 2016)
Nepal's trade balance in goods and services has been in deficit for many years. The large deficit has not resulted in a substantial accumulation of net foreign liabilities, as it has been largely financed with workers' remittances from abroad. Indeed, remittances are the largest component of the current account. This report aims at addressing the following questions: what are the underlying drivers of the trade imbalances and their relative contributions to the deficit (e.g. domestic private expenditure fueled by remittances versus public expenditures, relative prices, etc.)? What are the paths to be expected for the trade balance and the current account in the medium run, based on reasonable forecast assumptions for the main identified determinants? What are the implications of high remittances for the competitiveness in the short and long-run? How can Nepal maximize the positive impact of remittances in the economy? The authors assess the impact of remittances on Nepal's real exchange rate and attempt to distinguish between their short and long term impact. To conclude, efforts to increase savings and improve the allocation of remittances should also be accomplished through improvements in the overall investment climate and the business environment.